Associations of clinical and circulating metabolic biomarkers with low physical fitness and function in adults with chronic lymphocytic leukemia - Sitlinger, Andrea; Deal, Michael A.; Garcia, Erwin; Connelly, Margery; Thompson, Dana; Stewart, Tiffany; Macdonald, Grace; Hanson, Erik D.; Neely, Megan; Neely, Ben; Artese, Ashley; Weinberg, J. Brice; et al. (Frontiers in Oncology, 2022)
Many patients with chronic lymphocytic leukemia (CLL) experience physical dysfunction and low overall fitness. It remains unknown what factors drive CLL physical dysfunction. We assessed physical function and metabolic lipoprotein panels in 106 patients with CLL. In univariate analyses of clinical factors, a longer time since diagnosis was associated with a higher likelihood of dysfunctional aerobic fitness (OR=3.56, 95% CI: 1.37–9.22; p=0.002) and physical performance (SPPB: OR=2.03, 95% CI: 1.20–3.44; p=0.004). Having received treatment was associated with a higher likelihood of dysfunctional aerobic fitness (OR=1.57, 95% CI: 1.02–2.40; p=0.036), SPPB (OR=1.85, 95% CI: 1.13–3.03; p=0.011) and grip strength (OR=1.67, 95% CI: 1.10–2.55; p=0.015). We found several small HDL particle parameters, higher levels of citrate (OR=2.01, 95% CI: 1.22–3.31; p=0.030) and lower levels of hemoglobin (OR=0.50, 95% CI: 0.31–0.82; p=0.030) were associated with a higher likelihood of dysfunctional aerobic fitness. Multivariable LASSO-penalised regression analyses using variable importance measures (VIM) showed that 7.8nm HDL particles (VIM=1.000) and total HDL particle levels (VIM=1.000) were more informative than clinical measures for the odds of dysfunctional aerobic fitness and 6-minute walk functional fitness, respectively while 10.3nm HDL particles (VIM=0.383) were more informative for grip strength. Time since diagnosis (VIM=0.680) and having received treatment (VIM=0.490) were more informative than lipoprotein measures for the odds of having dysfunctional SPPB. Taken together, we establish significant relationships between clinical, metabolic factors and physical characteristics that might prompt early use of ancillary support services.